(untitled) (World Economics and Finance Bulletin, 2023)
The research aims to uncover the implications of adopting the costs of electricity production and the challenges faced by institutions when investing in clean energy resources for electricity production (sustainability costs) versus avoiding the costs of importing, environmental, social, wastage, and economic costs (unsustainability costs). The research applied the deductive approach as a literature review that addressed the research topic of renewable resources and the costs of electricity production. The most important conclusions indicated the necessity for institutions to focus on employing clean energy (solar energy as a source of electricity generation) and reducing the costs of fossil fuel consumption. Therefore, institutions should rely on proactive plans and feasibility studies to calculate the costs of employing clean energy that mimic the incurred costs and avoidance of clean energy costs.